Role of ZA and KCl Fertilizer on Growth and Yield of Red Ginger (Zingiber officinale var. Rubrum) - Supriyono Supriyono; A Y Darmawan; S Nyoto; M T S Budiastuti (Journal of Biodiversity and Biotechnology, 2023)
Red ginger is one of the commodities much needed by the people of Indonesia. The increase in public demand has not been matched by an increase in red ginger production. Efforts to increase red ginger production can be done with effective fertilization. This study aims to determine the appropriate dose of ZA+KCl fertilization for good growth and yield of red ginger. This research was conducted in March-August 2021 in the experimental area of Pelem, Wonorejo, Jatiyoso, Karanganyar, Central Java with coordinates 7°43'24.7”S 111°05'31.2”E with an altitude of 762  ASL. This study used a Randomized Completed Block Design (RCBD) with one factor and 4 treatments, namely D0 (control), D1 (ZA 225 kg.ha-1+KCl 50kg.ha-1), D2 (ZA 450 kg.ha-1+ KCl 100 kg.ha-1) and D3 (ZA 675 kg.ha-1+KCl 150 kg.ha-1) were repeated 6 times each. The results showed that the application of several doses of fertilizer did not increase plant height, number of leaves, dry weight of straw but could increase the number of tillers per clump by 37.11% and the number of tillers per plot by 27.10%. The results of regression analysis showed that D2 had a trend to increase fresh weight and storage weight of rhizomes with an average of 1.9 t.ha-1 and 1.5 t.ha-1. This research needs to be further developed by improving environmental influences to increase the growth and yield of red ginger.